2023
DOI: 10.1080/21645515.2023.2275475
|View full text |Cite
|
Sign up to set email alerts
|

Insights and expectations of healthcare professionals on the implementation of the updated pediatric regional immunization Calendar in Calabria, Italy

Sandro Giuffrida,
Giovanna Seta,
Antonio Gurnari
et al.

Abstract: The Regional Immunization Calendar in Calabria, a region of Italy, was updated in 2022, introducing optional co-administration of three injectable vaccines, with one oral vaccine, at 3 and 5 months old, and three injectable vaccines at 13–14 months old. In this project, the opinions and expectations of healthcare professionals (HCPs) in Calabria were investigated, with respect to the updated recommended practices. An 11-question survey was developed, which addressed concepts and topics related to immunization … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“… 39 The feasibility of full co-administration of pediatric vaccines, as recommended by the NVPP 2023–2025, 14 was documented in the Local Health Unit of Reggio Calabria at an Italian Continued Medical Education seminar in April 2023. 40 Following the introduction of the option for full co-administration in the Calabria Immunization Calendar in April 2022, 15 the proportion of patients who had chosen for their child to receive full co-administration increased from 37.33% in May 2022 to 86.17% in March 2023. 40 Despite this, two surveys carried out among HCPs in Italy highlighted that the lack of information on vaccine co-administration provided in relevant data sheets is perceived as a key barrier to implementation, 15 , 16 although this may have been overcome by the subsequent updated NVPP 2023–2025 recommendations.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“… 39 The feasibility of full co-administration of pediatric vaccines, as recommended by the NVPP 2023–2025, 14 was documented in the Local Health Unit of Reggio Calabria at an Italian Continued Medical Education seminar in April 2023. 40 Following the introduction of the option for full co-administration in the Calabria Immunization Calendar in April 2022, 15 the proportion of patients who had chosen for their child to receive full co-administration increased from 37.33% in May 2022 to 86.17% in March 2023. 40 Despite this, two surveys carried out among HCPs in Italy highlighted that the lack of information on vaccine co-administration provided in relevant data sheets is perceived as a key barrier to implementation, 15 , 16 although this may have been overcome by the subsequent updated NVPP 2023–2025 recommendations.…”
Section: Discussionmentioning
confidence: 99%
“… 2 A survey conducted in Calabria, Italy, in 2022, reported that the majority of healthcare professionals (HCPs) supported vaccine co-administration as an effective strategy to improve immunization calendars, as it can provide a range of benefits to healthcare systems and patients. 15 However, concerns were raised regarding the lack of readily available information on the safety of concomitant administration of multiple vaccines in pediatric populations, which could limit the implementation of coadministration strategies. 15 In particular, HCPs noted that limited safety data on co-administration of vaccines was often perceived as a key barrier, limiting its use in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations